Thicker than oil : America's uneasy partnership with Saudi Arabia - Bronson, Rachel (Oxford ; New York : Oxford University Press, 2006)
For fifty-five years, the United States and Saudi Arabia were solid partners. Since 9/11 this partnership has been sorely tested. In "Thicker than Oil", Rachel Bronson shows why the partnership became so intimate and the problems that it spawned. This normally secretive relationship comes alive with stories of American diplomats heaped on the floor before the Saudi King - and a bizarre request for the Saudi government to subsidize Polish pork exports, a request the U.S. Ambassador refused to deliver. Drawing on a wide range of archival material, declassified documents, and interviews with leading Saudi and American officials, Bronson chronicles a long history of close contact. Contrary to popular belief, Bronson shows that the relationship was never just about "oil for security." Saudi Arabia's religiously motivated foreign policy was deemed an asset when fighting "godless communism," as was Saudi Arabia's geographic location. From Africa to Afghanistan, Egypt to Nicaragua the two worked to beat back Soviet influence. Overlapping strategic interests helped compartmentalized differences around issues such as the Arab-Israeli conflict.; But decisions taken for hard headed Cold War purposes left behind a legacy that today enflames the Middle East. In today's fight against terrorism, Saudi Arabia is both part of the problem and part of the solution. Not withstanding real troubles, Bronson outlines the dangers of allowing the relationship to further deteriorate. Saudi Arabia, she notes, faces a violent and zealous opposition. If this opposition gains complete control of the state's huge resources, it will direct its efforts towards destroying the United States, auguring a true clash of civilizations.
Oil, God and real estate -- Dropping anchors in the Middle East -- An Islamic pope -- Shifting sands -- Double, double, oil and trouble -- "A new and glorious chapter" -- Mobilizing religion -- Begin or Reagan -- "We support some, they support some" -- The Cold War ends with a bang -- Parting ways -- September 11 and beyond -- Reconfiguring the U.S.-Saudi strategic partnership.
"A Council on Foreign Relations book."
Includes bibliographical references (pages 311-331) and index.
Print version record.
eBooks on EBSCOhost
Keywords: United States -- Foreign relations -- Saudi Arabia; Saudi Arabia -- Foreign relations -- United States; États-Unis -- Relations extérieures -- Arabie saoudite; Arabie saoudite -- Relations extérieures -- États-Unis.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; Diplomatic relations; Saudi Arabia; United States; Buitenlandse betrekkingen; Diplomatieke betrekkingen